Synthesis and biological activities of new pyrrolocarbazole-imidazobenzimidazole conjugates. Issue 30 (23rd July 2020) - Anizon, Fabrice; Giraud, Francis; Ivanova, Ekaterina S.; Kaluzhny, Dmitry N.; Shtil, Alexander A.; Cisnetti, Federico; Moreau, Pascale
Graphical abstract: Highlights: New pyrrolocarbazole-imidazobenzimidazole conjugates were prepared. Compounds 3, 6 and 13 exhibited sub-micromolar Pim-1 inhibitory potencies. Conjugation could enhance the antiproliferative potency of conjugates. Abstract: New pyrrolocarbazole-imidazobenzimidazole conjugates were prepared and evaluated for their inhibitory potencies toward Pim-1 kinase, DNA binding and antiproliferative activities against human tumor cell lines. The results demonstrated that conjugation of pyrrolocarbazole Pim inhibitors with imidazobenzimidazole derivatives could enhance the antiproliferative potency of conjugates compared to the derived compounds.